Prognosis of patients with ischaemic cardiomyopathy after coronary revascularisation: relation to viability and improvement in left ventricular ejection fraction. Issue 15 (13th May 2009) - Rizzello, V; Poldermans, D; Biagini, E; Schinkel, A F L; Boersma, E; Boccanelli, A; Marwick, T; Roelandt, J R T C; Bax, J J
Abstract : Background: In patients with ischaemic cardiomyopathy and viable myocardium, left ventricular ejection fraction (LVEF) does not always improve after revascularisation. Whether this may affect prognosis is unclear. Objective: To evaluate the prognosis of viable patients with and without improvement of LVEF after coronary revascularisation. Methods: Before revascularisation, radionuclide ventriculography (RNV) and dobutamine stress echocardiography were performed to assess LVEF and myocardial viability, respectively. Nine to 12 months after revascularisation, LVEF improvement was assessed by RNV. Patients were divided into three groups: group 1, viable patients with LVEF improvement (n = 27); group 2, viable patients without LVEF improvement (n = 15), group 3, non-viable patients (n = 48). Cardiac events were evaluated during a 4-year follow-up. Results: After revascularisation, the mean (SD) LVEF improved from 32 (9)% to 42 (10)% in group 1, but did not change significantly in group 2 and in group 3, p<0.001 by analysis of variance (ANOVA). Heart failure symptoms improved in both groups 1 (mean (SD) NYHA class from 3.1 (0.9) to 1.7 (0.7)) and 2 (from 3.2 (0.7) to 1.7 (0.9)), but not in group 3 (from 2.8 (1.0) to 2.7 (0.5)), p<0.001 by ANOVA. During follow-up, the cardiac event rate was low (4%) in group 1, intermediate (21%) in group 2 and high (33%) in group 3 (p = 0.01). Conclusion: The best prognosis after revascularisation may be expected in those viable patients whose LVEF improves. Conversely, viable patients without functional improvement have an intermediate prognosis.